Dynamics of Islamic Law: The Role of Fiqh Principles and Rules in Contemporary Issues - Eko Widiansyah; Riza Aulia (Program Pascasarjana UIN Sumatera Utara Medan, 2025)
Islamic law is a legal system derived from revelation and has unique characteristics that distinguish it from other legal systems. This study aims to analyze the basic principles and fundamental rules of Islamic law that serve as the basis for establishing and implementing law. The method used is qualitative research with a normative approach through a review of classical and contemporary literature. The results of the study indicate that the basic principles of Islamic law include justice (al-'adl), benefit (al-maslahah), legal certainty, and flexibility in responding to developments. Meanwhile, the rules of Islamic jurisprudence such as al-umur bi maqaṣidiha, al-ḍarar yuzal, al-yaqin la yazulu bi al-shakk, al-mashaqqah tajlib al-taysir, and al-'adah muḥakkamah play an important role in building a systematic and applicable legal framework. These principles and rules serve not only as guidelines for legal istinbaṭ but also as instruments for addressing contemporary legal issues contextually. Therefore, a comprehensive understanding of the basic principles and rules of Islamic law is crucial for realizing laws that are just, relevant, and responsive to societal dynamics.